To study efficacy of foot temperature monitoring and footprint study in preventing diabetic foot ulcer in type 2 diabetic patients with peripheral neuropathy - Manjunath Ashok Kolachi; Sudhir Kumar; Albail Singh Yadav; Mandavi Agarwal (Asian Journal of Medical Sciences)
Background: Diabetic foot ulcers (DFU) are a common complication among diabetic patients, leading to an increased risk of amputation and mortality. About 15–25% of diabetics develop DFUs, with half of these cases requiring amputation. Early identification of high-risk patients, particularly those with peripheral neuropathy, is crucial in preventing DFUs. Non-invasive methods such as foot temperature monitoring and footprint analysis have shown promise in identifying these high-risk individuals.